Diskursus Politik dalam Khazanah Keilmuan Islam - Iqbal, Imam (UIN Sunan Kalijaga Yogyakarta, 2019)
Islamic Studies are very rich in political thoughts and theories. Theoretically, this field has not been much explored, introduced, and developed by modern Muslim thinkers, although practically, Islam is closely related to politics since the early period of its birth. This paper examines and maps the theoretical discourse of politics that developed in the Islamic Studies. There are two issues that are the subject of discussion, namely: first, about the development of political theoretical discourse in Islamic Studies; and second, about the characteristics of the Islamic political discourse. From a descriptive- analytical view, it was found that discourse on politics in the Islamic Studies to the Middle Ages was discussed in two different genres, namely in the discipline of fiqh and philosophy. Each of these genres has different perspectives, approaches, ethical sources, and exponents. Although these two genres are different, they both emphasize the significance of ethics in politics or make ethics a character and basis on which politics is upheld.